The Pathogenic Roles of IL-22 in Colitis: Its Transcription Regulation by Musculin in T Helper Subsets and Innate Lymphoid Cells - Yan, Jun; Yu, Jing; Liu, Ke; Liu, Yijia; Mao, Changchuin; Gao, Wenda (Frontiers in Immunology, 2021)
IL-22 plays a crucial role in promoting inflammation, antimicrobial immunity and tissue repair at barrier surfaces. The role of IL-22 in colitis is still controversial: while IL-22 has a protective effect on gut epithelium in acute injuries, it also enhances colitis in a context-dependent manner. Here, we summarize the Yin and Yang of IL-22 in colitis. Particularly, we emphasize the role of innate lymphoid cells (ILCs) in IL-22 production and regulation. A previously underappreciated transcription factor, Musculin (MSC), has been recently identified to be expressed in not only Th17 cells, but also RORγt+/Id2+ IL-22-producing group 3 ILCs in the gut of naïve mice. We hypothesize that the co-expression and interaction of MSC with the key transcription repressor Id2 in developing lymphoid cells (e.g., in LTi cells) and ILC precursors might fine tune the developmental programs or regulate the plasticity of adaptive Th subset and innate ILCs. The much-elevated expression of IL-22 in MSC-/- ILC3s suggests that MSC may function as: 1) a transcription suppressor for cytokines, particularly for IL-22, and/or 2) a gatekeeper for specific lineages of Th cells and innate ILCs as well. Amelioration of colitis symptoms in MSC-/- mice by IL-22-blocking agent IL-22BP-Fc suggests a counterintuitive pathogenic role of IL-22 in the absence of MSC as a checkpoint. The theory that exuberant production of IL-22 under pathological conditions (e.g., in human inflammatory bowel disease, IBD) may cause epithelial inflammation due to endoplasmic reticulum (ER) stress response is worth further investigation. Rheostatic regulation of IL-22 may be of therapeutic value to restore homeostatic balance and promote intestinal health in human colitis.